Efektivitas Kebijakan E-Government dalam Pelaporan Infrastruktur Publik: Studi pada Aplikasi Silat Jantan - Aldiansyah Dwi Putra Husada; Galih Wahyu Pradana; Ericho Rizal Ardana (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Infrastructure development often faces challenges, especially with manual and unintegrated reporting systems. Manual reporting is time-consuming, prone to errors, and difficult for stakeholders to access, leading to supervision issues, budget misuse, and project delays. To address these problems, integrated digital reporting systems offer a promising solution to improve efficiency, transparency, and accountability. This study evaluates the effectiveness of the SILAT JANTAN application in supporting road infrastructure damage reporting in Kabupaten Madiun. Using a qualitative descriptive approach, data were gathered through in-depth interviews, field observations, and document analysis. The study applies the Technology Acceptance Model (TAM), focusing on perceived usefulness and ease of use by application users. Results indicate that SILAT JANTAN enhances reporting effectiveness, although challenges such as limited socialization and community participation remain. Recommendations include improving socialization, user training, and system strengthening to support sustainable technology adoption. This research aims to guide the development of a more effective and efficient digital reporting system to improve public services in Kabupaten Madiun.